الكرامية: تاريخها، فِرقها، وعقائدها: Al-Karramiyyah: History, Sect, and Belief - Jamshid bin Gholam bin Ali Rakhshani (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
The Karramiyyah is a sect that affiliates itself with Ahlus Sunnah wal Jama'ah, affirming the attributes of Allah (SWT). They follow Imam Abu Hanifah (rahimahullah) in matters of jurisprudence (fiqh), but they hold deviations in their creed that contradict the beliefs of Ahlus Sunnah wal Jama'ah, including Imam Abu Hanifah and his senior students. The sect comprises various groups and branches, centered primarily around Khurasan. Though they are now extinct, their teachings continue to influence some groups and sects, such as the Musyabbihah, Jahmiyyah, and Murji'ah. This study explores the Karramiyyah sect, detailing its history, beliefs, and the sub-sects within it.